PROBLEMATIKA PELAKSANAAN KONTRAK PENEMPATAN KIOS PASAR LEGI KOTA SURAKARTA PASCA KEBAKARAN - Pambuko Bayu Laksono; Putri Maha Dewi; Ashinta Sekar Bidari (Sekolah Tinggi Pariwisata Mataram, 2022)
The problem of decreasing the area of ​​kiosks and traders not willing to pay market fees is a serious obstacle for the market management agency. The distribution of kiosks or market stalls after construction is complete is constrained by traders who do not accept that their kiosks are reduced in size, and traders do not want to pay retribution because there are no buyers. The Market Management Office tries to socialize with traders who feel aggrieved by the reduced size of the kiosk so that the problem of reducing the size of the kiosk or booth is resolved, then the market management service also improves regarding the complaints of traders, namely the lack of buyers by evaluating the factors that the market lacks after it has been built, such as facilities and equipment. infrastructure contained in market buildings that are not met properly.